Answer:
the product is equal to the number. When a positive whole number is multiplied by a fraction greater than 1. When a positive whole number is multiplied by a fraction between 0 and 1, the product is less than the whole number.
Step-by-step explanation:
The chord length is the same as the radius, so R^2 = 9.
Area = (1/2)(9)(pi/3 - sqrt(3)/2) = (3/4) (2 pi - 3 sqrt(3))
Answer:
![115\ white\ rose\ bushes](https://tex.z-dn.net/?f=115%5C%20white%5C%20rose%5C%20bushes)
Step-by-step explanation:
Let
x------> the number of pink roses bushes
y----> the number of white rose bushes
we know that
![\frac{x}{y} =\frac{12}{15}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7By%7D%20%3D%5Cfrac%7B12%7D%7B15%7D)
-----> equation A
![x=92](https://tex.z-dn.net/?f=x%3D92)
substitute the value of x in the equation A
![y=\frac{15}{12}(92)=115\ white\ rose\ bushes](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B15%7D%7B12%7D%2892%29%3D115%5C%20white%5C%20rose%5C%20bushes)
Answer:
3. Correlation coefficients can be represented by the variable r
Step-by-step explanation:
Correlation coefficients show if there is a strong or weak positive or negative relationship, or if there is no relationship between the variables.
Correlation coefficients are negative when the relationship is inversely proportional and positive when the relationship is proportional.
Correlation coefficients can be any value less than or equal to 1 or greater than or equal to -1.
Answer:
Reflection across y axis
Translate up by 3 units
Step-by-step explanation:
Given
![f(x) = x + 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%20%2B%201)
![g(x) = -x + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%204)
Required
Describe the transformation from f(x) to g(x)
First, take a reflection of f(x) across the y axis.
So f(x) becomes f(-x)
when reflected
![f(-x) = -x +1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%20-x%20%2B1)
Next, translate f(-x) up by 3 units to give g(x)
![g(x) = f(-x) + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28-x%29%20%2B%20k)
Where
![k = 3](https://tex.z-dn.net/?f=k%20%3D%203)
![f(-x) = -x +1](https://tex.z-dn.net/?f=f%28-x%29%20%3D%20-x%20%2B1)
![g(x) = -x + 1 + 3](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%201%20%2B%203)
![g(x) = -x + 4](https://tex.z-dn.net/?f=g%28x%29%20%3D%20-x%20%2B%204)
Hence, the transformation from f(x) to g(x) includes:
Reflection across y axis
Translate up by 3 units